Libraries of Ukraine during the war - Musiienko, A. (ХДАК, 2023)
During World War II, the libraries of Ukraine suffered significant damage and losses due to military actions, bombings, and looting by the occupying German forces. The Nazis considered the destruction of libraries as a means of erasing the cultural and intellectual identity of the occupied territories and imposing their ideology on the local population. Despite the destruction and losses, some libraries managed to preserve their collections and even continue to function during the war. For example, the National Parliamentary Library of Ukraine in Lviv continued to operate, and its staff risked their lives to save valuable books and documents.
Keywords: бібліотеки України; libraries of Ukraine